Pore Structure and Synergy in Antimicrobial Peptides of the Magainin Family - Pino-Angeles, Almudena (PLoS Comput Biol, 2016)
Magainin 2 and PGLa are among the best-studied cationic antimicrobial peptides. They bind preferentially to negatively charged membranes and apparently cause their disruption by the formation of transmembrane pores, whose detailed structure is still unclear. Here we report the results of 5–9 μs all-atom molecular dynamics simulations starting from tetrameric transmembrane helical bundles of these two peptides, as well as their stoichiometric mixture, and the analog MG-H2 in DMPC or 3:1 DMPC/DMPG membranes. The simulations produce pore structures that appear converged, although some effect of the starting peptide arrangement (parallel vs. antiparallel) is still observed on this timescale. The peptides remain mostly helical and adopt tilted orientations. The calculated tilt angles for PGLa are in excellent agreement with recent solid state NMR experiments. The antiparallel dimer structure in the magainin 2 simulations resembles previously determined NMR and crystal structures. More transmembrane orientations and a larger and more ordered pore are seen in the 1:1 heterotetramer with an antiparallel helix arrangement. Insights into the mechanism of synergy between these two peptides are obtained via implicit solvent modeling of homo- and heterodimers and analysis of interactions in the atomistic simulations. This analysis suggests stronger pairwise interactions in the heterodimer than in the two homodimers.